Strategi Coping Stres Akademik dan Pola Perilaku Belajar Siswa SMA dalam Menghadapi Ujian Tulis dan Tugas Sekolah - Hesti Wardani (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
This study aims to analyze academic stress coping strategies and learning behavior patterns of senior high school students in facing written exams and school assignments. Academic stress arises when academic demands exceed students’ capacity to manage time, complete assignments, and meet environmental expectations. Coping strategies include problem focused coping, emphasizing problem solving through study planning, time management, and prioritization, and emotion focused coping, emphasizing emotional regulation through relaxation, self talk, prayer, and social support. Learning behavior patterns also significantly influence stress levels, with procrastination and ineffective time management increasing the risk of academic stress. Literature synthesis indicates that effective self management combined with adaptive environmental support can reduce academic stress and foster productive learning behavior. Additionally, gender differences affect coping strategy selection, with male students favoring cognitive strategies while female students balance cognitive and emotional spiritual approaches. The study highlights the importance of integrating adaptive coping strategies, structured learning behavior, and institutional support to enhance high school students’ academic readiness and psychological well being.